Novel Biomarkers of Acute Kidney Injury in the General Adult ICU: A Review. (May 2013) - Kokkoris, Stelios; Pipili, Chrysoula; Grapsa, Eirini; Kyprianou, Theodoros; Nanas, Serafim
<x xml:space="preserve">Abstract</x> Acute kidney injury is one of the most frequent problems occurring in the critically ill patients of the intensive care units and it is well established that it increases both morbidity and mortality in these patients. Moreover, despite technological and pharmaceutical advances during the last decades, the incidence as well as the mortality associated with acute kidney injury in these patients remains unchanged. Creatinine, the most common renal dysfunction biomarker in use, has many disadvantages, such as time delay in its increase and the influence by other factors on its serum concentration, such as age, gender, muscle mass, etc. Hence, the need for better renal biomarkers in order to timely intervene for acute kidney injury prevention is imperative. The lack of an early biomarker is an obstacle for the development of new acute kidney injury prevention strategies. With the incidence of acute kidney injury reaching epidemic dimensions, the need for novel markers is urgent. During the last years, the research for finding such biomarkers has been intense. The purpose of the present article is to review the studies which have tested the predictive ability of those markers (in urine and/or plasma) for early detection of acute kidney injury in the mixed adult intensive care unit population and underline the potential limitations encountered in the various studies.